2014
DOI: 10.1016/j.celrep.2014.08.071
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine Plays a Critical Role in Glioblastomagenesis by Recruiting the CHTOP-Methylosome Complex

Abstract: The development of cancer is driven not only by genetic mutations but also by epigenetic alterations. Here, we show that TET1-mediated production of 5-hydroxymethylcytosine (5hmC) is required for the tumorigenicity of glioblastoma cells. Furthermore, we demonstrate that chromatin target of PRMT1 (CHTOP) binds to 5hmC. We found that CHTOP is associated with an arginine methyltransferase complex, termed the methylosome, and that this promotes the PRMT1-mediated methylation of arginine 3 of histone H4 (H4R3) in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 60 publications
3
113
0
1
Order By: Relevance
“…Cell Culture and SILAC Labeling-GB2 cells were originally established from the tumor tissues classified as primary glioblastoma in the University of Tokyo Hospital with informed consent and approved by the Research Ethics Committee at the Institute of Medical Science, the University of Tokyo as previously reported (15)(16)(17)(18). The cells were cultured in the serum-free condition consisting of Dulbecco's modified Eagle's medium: Nutrient Mixture F-12 (DMEM/F12) media, B27 supplement without vitamin A (Life Technologies, Carlsbad, CA), EGF (20 ng/ml), and bFGF (20 ng/ml).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell Culture and SILAC Labeling-GB2 cells were originally established from the tumor tissues classified as primary glioblastoma in the University of Tokyo Hospital with informed consent and approved by the Research Ethics Committee at the Institute of Medical Science, the University of Tokyo as previously reported (15)(16)(17)(18). The cells were cultured in the serum-free condition consisting of Dulbecco's modified Eagle's medium: Nutrient Mixture F-12 (DMEM/F12) media, B27 supplement without vitamin A (Life Technologies, Carlsbad, CA), EGF (20 ng/ml), and bFGF (20 ng/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Although the previous transcriptome and proteome analysis suggested some key molecules for maintenance of glioblastoma stem cell properties, the global changes of protein phosphorylation in serum-induced alteration remain unclear (13,14). Thus, we aimed to reveal the phosphoproteome dynamics in glioblastoma stem cells named GB2, which were established from the tumor tissues of the glioblastoma patient (15)(16)(17)(18). GB2 cells grow as neurospheres in serum-free culture and are classified into proneural-type glioblastoma stem cells based on the transcriptional profiles of 24-signature genes suggestive of proneural characteristics (16,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, 5hmC is mostly associated with euchromatin and an increase in 5hmC has been documented at the transcriptional start sites of expressed pluripotent genes in embryonic stem (ES) cells [Ficz et al 2011]. Analogous to modifications of histones, 5mC is bound by specific methylbinding proteins, presumably to translate the DNA methylation signal, and growing evidence suggests that 5hmC and possibly 5fC and 5caC, are functional intermediates that bind to a specific repertoire of proteins, although the identities of these proteins are only now becoming apparent [Takai et al 2014].…”
Section: Epigenetic Regulators As Promising Therapeutic Targets In Acmentioning
confidence: 99%
“…Additionally, Kroeze et al showed an independent association of high levels of 5hmC with poor survival in AML [48]. The global increase of 5hmC in proneural glioblastoma promotes expression of oncogenes by increased TET1 expression [49]. High levels of 5hmC due to high TET1 & 3 expression in hypoxic BTIC predicts poor disease-free and overall survival in breast cancer [41].…”
Section: Interplay Between 5-hydroxymethylcytosine and Cancermentioning
confidence: 99%